ENTRE O DISCURSO JURÍDICO E O POLÍTICO SOBRE O DIREITO À SAÚDE: uma análise dos atores, interesses e racionalidades - MIRANDA NETTO, Edson Barbosa de (2017)
The present research aimed to carry out a content analysis in legal and political speeches given in Brazil by the Presidents of the Republic, the Ministers of Health and the Federal Suprem Court of Justice from January 1, 2011 to October 15, 2016, in order to identify the frequency in which terms and expressions related to predetermined thematic categories appeared in the content of such discourses. Thus, it was sought to identify and analyze the actors, interests and rationalities of the Unified Health System. As the methodological procedure, the Lawrence Bardin’s content analysis was chosen in order to enable an understandment about the explicit or non apparent meanings in the juridical and political speeches content analyzed in this research. It was verified that the different frequencies express the rationalities and the concerns of each authority or organ analyzed, so that even important categories – such as the Health Judicialization and its serious reflexes in health services and the Reorganization of the public health competence distribution between the Federation members – had little or none appearance in the content of certain groups of speeches. The reason found to this was a predominant circumstantial feature in the content of the political speeches of the Executive authorities and the institutional limits of the Federal Suprem Court of Justice when confronted with political issues.